2018
DOI: 10.3892/ijmm.2018.3667
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of allograft inflammatory factor‑1 expression and secretion by macrophages stimulated with aldosterone promotes renal fibroblasts to a profibrotic phenotype

Abstract: Macrophages have been identified as a key cell type in the pathogenesis of renal interstitial fibrosis (RIF). However, the mechanism through which macrophages drive fibrosis remains unclear. The current study focuses on the effects and possible underlying mechanism of allograft inflammatory factor-1 (AIF-1), an inflammation-responsive scaffold protein expressed and secreted by macrophages, in promoting fibroblasts to a profibrotic phenotype. In vivo experiments indicated that AIF-1, CD68 and α-smooth muscle ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 72 publications
(85 reference statements)
4
8
0
Order By: Relevance
“…In our study, we found increased localization of α -SMA-positive cells in the SV. These results are in agreement with in vitro and in vivo studies that have shown areas of fibrosis-activated macrophages generating soluble mediators that modulate activation and proliferation of myofibroblasts [ 58 , 59 ]. Therefore, our findings suggest that cisplatin might promote the progression of SV fibrosis through the regulation of macrophage infiltration, secretion of IL-1 β , and accumulation of laminin and collagen IV.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, we found increased localization of α -SMA-positive cells in the SV. These results are in agreement with in vitro and in vivo studies that have shown areas of fibrosis-activated macrophages generating soluble mediators that modulate activation and proliferation of myofibroblasts [ 58 , 59 ]. Therefore, our findings suggest that cisplatin might promote the progression of SV fibrosis through the regulation of macrophage infiltration, secretion of IL-1 β , and accumulation of laminin and collagen IV.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the results of a previous study (3), the RAW264.7 macrophage cell line was selected to examine the potential effect of AIF-1 on the aldosterone-induced activation of the PI3K/AKT/mTOR pathway; these cells constitutively express low levels of AIF-1 and facilitate the positive selection of stable transfectants for AIF-1 gene overexpression and knockdown. The results showed that aldosterone increased the mRNA expression levels of PI3K, AKT and mTOR compared with those in the untreated cells.…”
Section: Resultsmentioning
confidence: 99%
“…The sections were examined using light microscopy, and images of 10 non-repeating visual fields were randomly captured (magnification, ×400). Immunohistochemistry was performed as described previously (3). For blocking the antigen, 5% bovine serum albumin was used for 20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations